PENGARUH PERKEMBANGAN PERKEBUNAN KELAPA SAWIT TERHADAP EKONOMI PEDESAAN DI KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU - Erma Yunita; Almasdi Syahza; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to analyze the effect of the development of oil palm plantations on rural economies surrounding communities in District Fullness Rokan Hulu. This research was conducted in the District Fullness Rokanhulu district. The method used is descriptive qualitative method. A population of 4,999 people by the farmers and sampled 98 oil palm growers. Data collection instrument used was a questionnaire with a sampling technique in this research is to use non-random sampling method is purposive sampling. From the research activities of oil palm plantations in the district Fullness Rokan Hulu creates a multiplier effect of 1.20 figures, especially in employment and business opportunity. Oil palm plantation activities have an impact acceleration of the economic development community in the effort to reduce poverty. Oil palm plantations can improve the economy of rural communities. Economically will create purchasing power, which in turn increases the demand for public goods.Keywords: Multiplier Effect, Rural Economy, Oil Palm Plantation1